Partnership in Higher Education on the New Silk Road (on the example of Al-Farabi KazNU) (Journal of Oriental Studies, 2016)
This article is about the development of cooperation in higher education in terms of mutual benefit for cooperation participants. It is assumed that the New Silk Road can be the way of knowledge and technology transfer. Theoretical background of mutual benefit in educational cooperation, even with unequal opportunities of participants, are the principles of the so-called neighborhood policy (on the example of Chinese and European Neighbourhood Policy). The author analyses Al-Farabi KazNU successfulexperience in international partnership. The article presents the main directions of international cooperation of the university, including in the regional context. The data on the inbound and outbound exchange students, Dual Degree Diploma programmes is provided.
Keywords: education; partnerships; internationalization; New Silk Road; mobility